MOBILE PRIVACY AWARENESS OF HIGHER EDUCATION STUDENTS IN PLATEAU STATE NIGERIA - Jegede, Abayomi; Chagga, Chagga Aku; Aimufua, Gilbert; Mazadu, Jesse; Oloyede, Ayodele; Olubodun, Kolawole (Jurnal Transformatika, 2023)
The ubiquitous nature of mobile devices and wide array of applications (and services) they offer make them useful in virtually all areas of human endeavours. Owners of mobile devices store large amounts of vital and sensitive personal information on their devices. Unauthorized access to such information by third parties can violate the privacy of users and expose individuals and businesses to huge financial loses and damage to reputation. This makes it imperative for owners of technology service providers and owners of mobile devices to take proactive steps that prevent privacy violation. One of such critical steps is privacy awareness, which is the knowledge and consciousness of the need for privacy, an understanding of actions that promote or compromise privacy and the consequences of irresponsible online behaviour. The aim of this study is to assess the level of awareness of tertiary institution students with respect to privacy issues associated with the use of mobile communication devices. The research uses questionnaires to obtain data on the privacy awareness of users of mobile devices in some tertiary institutions in Plateau State. The paper investigates the current status of mobile privacy issues and awareness of users in these tertiary institutions. It also attempts to expose the gaps in privacy awareness of mobile device users, the factors responsible for limited privacy awareness and strategies for addressing the low level of privacy awareness of mobile device users. The results from this study show that high level of literacy does not necessarily imply high-level privacy awareness. Many respondents who are privacy aware do not possess the necessary skills or knowledge to ensure data and user privacy on their mobile devices. Others who possess this knowledge are will to engage in practices that compromise privacy in exchange for financial gain. Overall, the study exposes the actual level of privacy awareness and defeat the assumption that high level of education automatically results in high-level privacy awareness. It also contradicts the assumption that being privacy-aware guarantees responsible online behaviour and adherence to practices that promote online privacy.